Relationship of Household Income, Age During Pregnancy and Low Birth Weight (LBW) - Teuku Muliadi; Marniati Marniati; Cukri Rahma; Sufyan Anwar; Fikri Faidul Jihad; Laila Apriani Hasanah Harahap; Hanif Muchdatul Ayunda (Universitas Teuku Umar, 2023)
Low birth weight (LBW) is still a major problem in developing countries including Indonesia. The prevalence of LBW tends to decrease from 2013-2018, from 8.6% to 6.51%. Therefore, it is necessary to analyze the relationship between maternal age at pregnancy and household income with the incidence of low birth weight. The type of the study was analytic observational with quantitative method. The population in this study were all mothers who had children aged 6-24 months who resided in West Aceh District and met the inclusion and exclusion criteria by means of simple random sampling. The dependent variable of this study was LB W while the independent variables were maternal age during pregnancy and family income. The risk tendency for each variable was seen using the OR (odds ratio) value which used a Confidence Interval of 95%. The results showed that there was a significant relationship (p=0.049) between the two variables. The amount of household income influences the quality of the mother's health and nutrition intake during pregnancy impacts the weight and health of the child born.